The CIA and Third Force movements in China during the early Cold War : the great American dream - Jeans, Roger B. (Lexington Books, 2018)
"This study examines the CIA's "third force" strategy--providing support for a third-party alternative over two primary on-the-ground options--in East Asia during the first decade of the Cold War. The author argues that the strategy failed due to a lack of understanding of the historical and cultural contexts of the region"--